GAYA BAHASA NIDĀ’ DALAM SURAT YUSUF (PENDEKATAN STILISTIKA) - Faqihuddin, Abdu Rabbi (Universitas Ahmad Dahlan)
The purpose of this study is to describe the form of nidÄ', kinds of munÄdÄ, and the meanings contained in the style of nidÄâ€™ language and kalÄm afterward. This research discusses the style of nidÄâ€™ with the object of Sura Yusuf, using stylistic analysis. The method used in this research is a qualitative descriptive method, which is library research. The problem raised in this research is how the form and kinds of nidÄâ€™ and munÄdÄ, the meaning of the style of nidaâ€™ and later kalam in the sura Yusuf. The results obtained in this research are, in the sura Yusuf there are two forms of nidÄâ€™, namely lafdziyyah and ghairu lafdziyyah, and three kinds munÄdÄ, namely mudhÄf, nakirah maqshÅ«dah, and mufrad alam. While the nidÄâ€™ in the sura Yusuf followed by four kalÄm namely amr, nahy, khabar, and istifhÄm with the meaning of haqÄ«qÄ« and majazÄ«Â